Assessing ageing resistance of chlorinated natural rubber gloves by thermoanalytical technique - Eng A H; Lai P F; Syahidah Y (Journal of Rubber Research, 2000)
Ageing resistance of chlorinated natural rubber gloves was evaluated by measuring its activation energy of oxidation, using differential scanning calorimetry technique. All the samples examinated were found to conform to the Kissingers equation. A linear correlation with the corresponding tensile retention data was found. However, the correlation with crosslink density ratio data was less linear. The significance of these observations was discussed.
Keywords: Ageing; Rubber gloves; Thermoanalytical technique